Community-based conservation - Cunningham, A.B.; Shanley, P. (2001)
This practice of community based conservation is discussed, specially social issues which are firmly embedded in the management of forest resources by communities, but too often overlooked. Good management requires not only technical expertise, but include wide social acceptance. Useful analytical frameworks for fieldworkers to better understand the complex issues surrounding community based resource management are described.